2022
DOI: 10.1158/1078-0432.ccr-22-1851
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Addiction of Fibrolamellar Hepatocellular Carcinoma to the Fusion Kinase DNAJB1-PRKACA

Abstract: Purpose: Gene fusions are drivers of many pediatric tumors. In fibrolamellar hepatocellular carcinoma (FLC), a fusion of DNAJB1 and PRKACA is the dominant recurrent mutation. Expression of the DNAJB1-PRKACA fusion gene in mice results in a tumor that recapitulates FLC. However, it is not known whether transient expression of DNAJB1-PRKACA is sufficient only to trigger tumor formation or whether ongoing expression is necessary for maintenance and progression. Experimental Design: We screened shRNAs tiled over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Once we could measure the FLC tumour growing in the mice, we induced production of the shRNA. The DNAJB1-PRKACA fusion disappeared from the cells, and the tumours stopped growing and then shrank 36 . The same virus and shRNA had no effect on other tumour types 36 .…”
Section: Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…Once we could measure the FLC tumour growing in the mice, we induced production of the shRNA. The DNAJB1-PRKACA fusion disappeared from the cells, and the tumours stopped growing and then shrank 36 . The same virus and shRNA had no effect on other tumour types 36 .…”
Section: Perspectivementioning
confidence: 99%
“…The DNAJB1-PRKACA fusion disappeared from the cells, and the tumours stopped growing and then shrank 36 . The same virus and shRNA had no effect on other tumour types 36 . This showed that DNAJB1-PRKACA was needed for the FLC tumour to continue to grow.…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…They uncovered that not only is DNAJB1-PRKACA sufficient for FLC development, but that it is required for tumor cells to survive. 12 They subsequently showed the efficacy in targeting DNAJB1-PRKACA with shRNA in human-relevant models, but translating this approach will require minimizing off-target effects of native PKA and ensuring effectiveness in situ. 12 Another group exploited the FLC-specific nature (i.e., exclusively in tumor cells) of the immunogenic neoepitopes from the DNAJ-PKAc chimera to pioneer an innovative immune targeting strategy.…”
Section: Introductionmentioning
confidence: 99%
“…12 They subsequently showed the efficacy in targeting DNAJB1-PRKACA with shRNA in human-relevant models, but translating this approach will require minimizing off-target effects of native PKA and ensuring effectiveness in situ. 12 Another group exploited the FLC-specific nature (i.e., exclusively in tumor cells) of the immunogenic neoepitopes from the DNAJ-PKAc chimera to pioneer an innovative immune targeting strategy. 13 The authors performed a series of elegant studies to reveal that a personalized chimeric protein-derived peptide vaccine in conjunction with a toll-like receptor 1/2 agonist resulted in sustained immune response in a patient with multiple prior recurrences.…”
Section: Introductionmentioning
confidence: 99%